2006
DOI: 10.1590/s1517-83822006000300030
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in Salmonella Enteritidis isolated from broiler carcasses

Abstract: Eighty Salmonella Enteritidis strains isolated from broiler carcasses between May 1995 and April 1996 in the State of Rio Grande do Sul, Brazil, were tested for antibiotic susceptibility using the disk diffusion method. Resistance to colistin, novobiocin, erythromycin and tetracycline was observed in 100% of the isolates. The strains showed intermediate resistance at different levels to kanamycin (1.25%), enrofloxacin (3.75%), neomycin (3.75%), fosfomycin (20%), sulphonamides (86.25%) and nitrofurantoin (90%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
28
4
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 20 publications
16
28
4
9
Order By: Relevance
“…On the other hand, none of the strains was resistant to chloramphenicol (Table 1), as previously reported by Cardoso et al (2006), Lima et al (2009), Begum et al (2010, and Galdino et al (2013). These authors also did not find any resistance to norfloxacin in Salmonella strains isolated from chicken products.…”
Section: Resultssupporting
confidence: 86%
“…On the other hand, none of the strains was resistant to chloramphenicol (Table 1), as previously reported by Cardoso et al (2006), Lima et al (2009), Begum et al (2010, and Galdino et al (2013). These authors also did not find any resistance to norfloxacin in Salmonella strains isolated from chicken products.…”
Section: Resultssupporting
confidence: 86%
“…Also, the result of Cardoso et al (2006) mentions, besides ciprofloxacin, the susceptibility to gentamicin, norfloxacin and sulfazotrin of strains isolated from chicken carcasses in the state of Rio Grande do Sul is similar to our results. Medeiros et al (2011), researching the resistance of 18 Salmonella serotypes isolated from frozen broiler carcasses in 15 Brazilian cities against antimicrobials, found that strains of S. enteritidis were resistant to all antibiotics tested, at various levels, including antimicrobials used in this study.…”
Section: Discussionsupporting
confidence: 90%
“…For example, a few studies were found reporting the isolation of salmonella serotypes with high-level resistance in Brazil (Silva and Duarte, 2002;Cardoso et al, 2006;Ribeiro et al, 2007;Souza et al, 2011), Spain (Carramiñana et al, 2004), Lithuania (Ruzauskas et al, 2005), Nigeria (Okolli et al, 2006), United States (Alali et al, 2010) and Greece (Sakaridis et al, 2011). These studies reported that Salmonella from poultry source are resistant to a wide range of antimicrobials and confirmed that poultry are important reservoirs of multidrug-resistant Salmonella.…”
Section: Introductionmentioning
confidence: 94%
“…Resistance to nitrofurantoin (32%), and streptomycin (16%) was low when compared to the 95% found by Cardoso et al (9) in S. Enteritidis, and the 100% found by Ribeiro et al (22) in S. Hadar.…”
Section: Resultsmentioning
confidence: 54%